Polyhydramnios of pregnant women and its relation with obstetric complications and perinatal disorders - Gaistruk, N. A.; Dubas, l. G.; Gaistruk, A. N.; Topolnitska, S. V. (Journal of Education, Health and Sport, 2017)
Paying attention to extremely high frequency and a huge variety of serious complications and consequences, pregnancy polyhydramnios is an important and urgent problem in obstetrics. Studies on this issue are mostly fragmented and focused mainly on the pathogenesis, diagnosis and treatment of disease, without revealing the molecular mechanisms of fetus distress. The relevance and practical importance of this work shows the fact that, except generalization and systematization of previous data there was conducted a detailed analysis of risk factors, prognosis of complications, given the prevention activities and also it focuses on comprehensive consideration of the problem and the need for cooperation between different sectors of medicine for better treatment and prevention of this pathology, which is an indisputable indicator of the importance of research.